Pertumbuhan Ekonomi dan Kesejahteraan Umat: Telaah Integratif antara Indikator Pendapatan Nasional dan Prinsip Ekonomi Syariah - Arifa Pratami; Ismail Ismail; Nurhudawi Nurhudawi; Annisa Aulia (IAIN Langsa, 2025)
This study aims to analyze the relationship between economic growth and community welfare through an integrative approach that combines national income indicators with Islamic economic principles based on maqasid al-shariah. This article constitutes a library-based study employing a qualitative approach, with descriptive analysis as the primary methodology. The findings indicate that conventional economic growth indicators such as Gross Domestic Product (GDP), Gross National Product (GNP), and per capita income do not fully reflect comprehensive community welfare, as they tend to overlook dimensions of distributive justice, ethics, and social benefit. The integration of macroeconomic indicators with maqasid al-shariah–based welfare parameters is therefore considered capable of providing a more holistic, inclusive, and welfare-oriented framework for development evaluation, aimed at achieving falah for the community.